Refleksi Teoritik Dan Konseptual Tentang Perlindungan Hukum Terhadap Anak Dalam Kajian Perundang-Undangan di Luar KUHP - Kumala Sari, Ratna; Kamalludin, Iqbal (Jurnal Komunikasi Hukum, 2021)
Legal protection for children must begin as early as possible, so that one day they can participate optimally for the development of the nation and state. Child protection is an embodiment of justice in a society, which must be endeavored in various fields of state and community life. This study aims to understand and examine the legal protection of children in the study of legislation outside the Criminal Code. This type of research used in this paper using the normative juridical approach method considering the problems studied and studied in addition to holding on to juridical aspects that is based on norms, regulations, legal theories. The specifications used in this study are analytical descriptive because this study is expected to obtain a clear, detailed and systematic picture. The results showed that the legal protection of children in the study of legislation outside the Criminal Code is regulated in Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection and Law of the Republic of IndonesiaÂ Number 11 of 2012 concerning Juvenile Justice System. Protection that is obliged to be given is legal protection both preventively to prevent disputes and repressively to resolve problems that occur. In addition, legal protection is given to children starting from the investigation stage to the implementation phase of decisions in Penitentiary.